Nokturnal of Mosquito Spesies in Sukawana, Curug District, Serang City, Banten - Jasmi, Riski Andrian; Hanin Irfathin Ardani; Hafaz Arif; Kholisotun Najwa; Najmah Fairuz Zahira; Azeng Nurul Hikmah; Royatul Atfaliyah; Juliyanti, Juliyanti; Gading Utoro Bambang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mosquitoes are members of the Culicidae family which act as vectors. Mosquitoes usually live in tropical environments, including Indonesia. This research aims to identify types of nocturnal mosquitoes in Sukawana, Serang City. The mosquito catching method is carried out using a sweeping technique at each period, then the mosquitoes caught are taken using a special aspirator. The proportion of mosquitoes most commonly found was Culex quinquefasciatus at 51 individuals (51%). Culex Fuscocephala as many as 31 individuals (31%), Culex perexiguus as many as 16 individuals (16%), and Aedes albopictus as many as 2 individuals (2%). This research provides important information regarding the presence of mosquito species in Sukawana, which can be used as initial data for efforts to control diseases transmitted by mosquitoes.